Spuren des Apokalyptischen bei Agamben und Hölderlin. - Deibl, Jakob Helmut (Münchener theologische Zeitschrift, 2024)
This text places Giorgio Agamben and Friedrich Hölderlin in relation to each other. The guiding categories are recapitulation and dislocation: the recovery of the whole at the end and its displacement. Not only are these two categories, as Martin Kirschner and others have demonstrated, fundamental elements of Agamben's Pauline-orientated messianic thinking, they also characterize the way in which he refers to Hölderlin. References to Hölderlin often appear at the end of Agamben's texts in order to modulate their overall meaning once again. Recapitulation and transposition are also, as Agamben illustrates using Hölderlin as an example, motifs that characterize the rhyme and verse structure of poetry in general. This becomes evident in an analysis of Hölderlin's verse "But where there is danger, the saving also grows." (Patmos). In "Il tempo che resta" from 2000, Agamben interpreted the rupture of the rhyme and structure of poetry in Hölderlin's free-rhythmic hymns as a break with the messianic tradition of thinking the divine. What is new in his 2021 book "La follia di Hölderlin," is the extension of these considerations to Hölderlin's poems of the tower period, which once again adopt rhyme and certain order structures. He sees this as a transition to an anti-tragic, comedic consciousness. In addition, I attempt to interpret Hölderlin's later poems -- in a stronger continuity with the free-rhythmic hymns -- as a continued search for open spaces.